2006
DOI: 10.1007/s10544-006-7710-x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-based microfluidic platform for biomolecular separation

Abstract: A novel microfluidic platform for manipulation of micro/nano magnetic particles was designed, fabricated and tested for applications dealing with biomolecular separation. Recently, magnetic immunomagnetic cell separation has attracted a noticeable attention due to the high selectivity of such separation methods. Strong magnetic field gradients can be developed along the entire wire, and the miniaturized size of these current-carrying conductors strongly enhances the magnetic field gradient and therefore produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 6 publications
0
43
0
Order By: Relevance
“…For example, microscale core/coil design [3], current-carrying wires [4], wire matrix [5], and micropatterned conductors [6] have been used for trapping, transport, and catch-and-release of magnetic beads. However, micro-electromagnetic systems are limited to manipulation of small numbers of beads and with low magnetic forces due to Joule heating and complexity concerns.…”
Section: Open Accessmentioning
confidence: 99%
“…For example, microscale core/coil design [3], current-carrying wires [4], wire matrix [5], and micropatterned conductors [6] have been used for trapping, transport, and catch-and-release of magnetic beads. However, micro-electromagnetic systems are limited to manipulation of small numbers of beads and with low magnetic forces due to Joule heating and complexity concerns.…”
Section: Open Accessmentioning
confidence: 99%
“…Photolithographic techniques enable fabrication of almost any desired MET geometry; as a result the geometry of an MET can be tuned for a specific application. Ramadan et al [18,[21][22][23][24][25][26][27] and Lee et al [20,28] have demonstrated customized MP traps which emphasize the effects of different MET geometries. Simulations of magnetic fields produced by different MET geometries have magnetic field profiles attributed to the shape of the MET and magnetic coupling between conductors or loops.…”
Section: Geometrymentioning
confidence: 99%
“…These devices can be categorized into discrete and continuous separator. Discrete separator usually needs three steps (i.e., trap, washing and elution) to complete separation (Choi et al 2002;Drogoff et al 2008;Guo et al 2006;Jiang et al 2006;Lund-Olesen et al 2007;Ramadan et al 2006;Ramadan et al 2009;Smistrup et al 2005). For example, Choi et al (2002) proposed the first on-chip magnetic bead-based immunoassay for protein analysis by utilizing integrated electromagnets.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic force generated by electromagnetic microcoils is usually small. To strengthen the magnetic force, electromagnetic microcoils are integrated with magnetic materials at the center by complicated fabrications (Drogoff et al 2008;Ramadan et al 2006;Smistrup et al 2005). However, for these magnetophoretic separators high efficient separation needs large electric current and thus leads to obvious joule heating which would cause unwanted effect in microfluidic devices.…”
Section: Introductionmentioning
confidence: 99%